Environmental Determinants of Behavioral Intention to Adopt Electric Vehicles in Vietnam - Nguyen, Nam Khoa; Nguyen, Thi Hai Linh (International Review of Management and Marketing, 2026)
This research examines Vietnamese consumers’ intention to adopt EVs by extending the Theory of Planned Behavior with three environmental variables: environmental knowledge, environmental concern, and environmental responsibility. A sample of 545 valid responses based on an online survey was analyzed and the research model was analyzed using structural equation modeling. The extended model explains 42.4% of the variance in behavioral intention, indicating a relatively strong explanatory power. The results show that environmental knowledge, environmental concern, and environmental responsibility significantly influence behavioral intention directly as well as indirectly via attitude, subjective norms, and perceived behavioral control. All core constructs of the Theory of Planned Behavior also exert positive effects on behavioral intention, with perceived behavioral control emerging as the strongest predictor (β = 0.322). These findings underscore the significance of incorporating environmental factors into models of behavior and offer practical implications for policymakers and promotors aiming to enhance sustainable mobility adoption.